Chemoselective crossed acyloin condensations: catalyst and substrate control - CONNON, STEPHEN (My University, 2011)
The interplay between catalyst and substrate control in crossed acyloin condensation reactions has been studied. It was found that a pentafluorophenyl-substituted triazolium ion derived catalyst was capable of catalyzing highly chemoselective processes between a range of aliphatic and aromatic aldehydes utilized in a 1:1 ratio.
PUBLISHED
Keywords: Organic chemistry; aliphatic and aromatic aldehydes